Optimization of Bending and Compressive Strength Behavior of Agave americana Fiber Reinforced Cementitious Composite Using Response Surface Methodology - Deghboudj, Samir; Boukhedena, Wafia; Satha, Hamid (Periodica Polytechnica Civil Engineering, 2023)
The purpose of this research is to optimize several variables, including fiber length, volumetric fiber percentage, and sodium hydroxide (NaOH) solution concentration, which influence the bending and compression behavior of cementitious composites reinforced with plant-based fibers from Agave americana. Samples of composites based on fibers extracted from Agave americana and a cement matrix were manufactured and prepared according to a reference mortar. Box-Behnken Design (BBD) of Response Surface Methodology (RSM) was employed to build an experimental design to explore their mechanical behavior and to construct a set of mathematical models predictive of their behavior. The first stage of the work includes the extraction and processing of Agave americana fibers and the preparation of cement and Agave americana mortar specimens. The second phase aims to establish mathematical models to forecast the workability of the cement mortar and its strength at 28 days while emphasizing the correlations and interactions between the different components through the Design Expert software.